2016
DOI: 10.1016/j.ajog.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of circulating proteins in early pregnancy with preterm birth

Abstract: BACKGROUND Preterm birth (PTB) (<37 completed weeks gestation) is a pathological outcome of pregnancy and a major global health problem. Babies born preterm have an elevated risk for long term adverse medical and neurodevelopmental sequelae. Substantial evidence implicates intrauterine infection and/or inflammation in PTB. However, these are often relatively late findings in the process, when PTB is inevitable. Identification of earlier markers of PTB may make successful intervention possible. Although select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
6
30
0
Order By: Relevance
“…Specifically women in the upper quartile of C3a were three times more likely to have an adverse outcome later in pregnancy after controlling for parity and pre-pregnancy BMI compared to women in any lower quartiles. In a recent biomarker discovery study, Lynch and colleagues (Lynch, Wagner, Deterding, et al, 2016) also found that the complement factors B and H along with coagulation factors IX and IXab were the highest ranking proteins found in cases of PTB compared to term controls, suggesting that the leading pathways to PTB include the complement, immune and clotting systems. Similarly women with elevated levels of the complement factor Bb in early pregnancy were nearly four times as likely to have PTB after controlling for known PTB related risk factors (Lynch et al, 2008).…”
Section: The Microbiome As a Mechanism For Preterm Birthmentioning
confidence: 98%
“…Specifically women in the upper quartile of C3a were three times more likely to have an adverse outcome later in pregnancy after controlling for parity and pre-pregnancy BMI compared to women in any lower quartiles. In a recent biomarker discovery study, Lynch and colleagues (Lynch, Wagner, Deterding, et al, 2016) also found that the complement factors B and H along with coagulation factors IX and IXab were the highest ranking proteins found in cases of PTB compared to term controls, suggesting that the leading pathways to PTB include the complement, immune and clotting systems. Similarly women with elevated levels of the complement factor Bb in early pregnancy were nearly four times as likely to have PTB after controlling for known PTB related risk factors (Lynch et al, 2008).…”
Section: The Microbiome As a Mechanism For Preterm Birthmentioning
confidence: 98%
“…The same applies to Pappalysin-1 (PAPP-A), one of the top nine proteins whose concentration increased more than five-fold in this study. PAPP-A is mainly produced by the placenta, and its concentration is low in the first trimester of pregnancies complicated by either chromosomal abnormalities (Trisomies 21, 18 and 13, and monosomy X) (93, 97-100, [245][246][247][248] or a subset destined to develop placenta-mediated obstetrical syndromes such as SGA and preeclampsia (119, [249][250][251][252][253][254][255][256][257][258][259][260][261] and preterm birth (262). In this study, we also report the longitudinal changes in the plasma concentrations of PAPP-A as a function of gestational age.…”
Section: Meaning Of the Studymentioning
confidence: 99%
“…Plasma samples were divided into aliquots and stored at 280°C in a Biorepository at the University of Colorado Hospital. Details of the cohort have been described by Lynch et al (25).…”
Section: The Denver Baby Blanket Cohortmentioning
confidence: 99%